2020
DOI: 10.1155/2020/2048756
|View full text |Cite
|
Sign up to set email alerts
|

Co-Supplementation of Flos Sophorae Extract with Tremella fuciformis Polysaccharides Improves Physicochemical, Textural, Rheological, and Antioxidant Properties of Low-Fat Yogurts

Abstract: Flos Sophorae extract (FSE) with abundant rutin and Tremella fuciformis polysaccharides (TP) could act as novel natural improvers of low-fat yogurt due to their health benefits and properties of interacting with proteins. This study attempted to understand how FSE or its combination with TP influences physicochemical, textural, and antioxidant properties of low-fat yogurts. The results indicated that the low concentrations of FSE (1.2 or 2.4%) increased the antioxidant activity, prompted the S. thermophilus gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…1,406 AD), FFB-SJ consumption was recorded in “Jiu Huang Ben Cao” ( Zhu et al, 2015 ). FFB-SJ is increasingly used in the food industry, including as a preservative in sausages ( Tang et al, 2019 ), additives for color and flavor in rice wine ( Yang et al, 2021 ), components of the fat structure in yogurt ( Tang et al, 2020 ), and as an edible packaging film material ( Guo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…1,406 AD), FFB-SJ consumption was recorded in “Jiu Huang Ben Cao” ( Zhu et al, 2015 ). FFB-SJ is increasingly used in the food industry, including as a preservative in sausages ( Tang et al, 2019 ), additives for color and flavor in rice wine ( Yang et al, 2021 ), components of the fat structure in yogurt ( Tang et al, 2020 ), and as an edible packaging film material ( Guo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is speculated that the increase in SDS and RS contents in noodles after adding TF may be related to the components of polysaccharide and dietary fiber in TF. Meanwhile, the rheological properties of the TF solution, shown in Figures S1 and S2 , also showed that the TF solution had good viscosity and exhibited an elastic characteristic similar to weak gel-like behavior, which may affect the binding of digestive enzymes to the active sites, leading to a decrease in the digestibility of starch and an increase in resistant starch content [ 8 , 13 ]. The gel network formed by introducing appropriate amounts of hydrocolloids interacts with starch and protein, stabilizes the structure of starch granules, decreases the degree of starch granules swelling, and entraps starch granules into a physical barrier to reduce starch digestibility [ 10 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…Its chemical components are often extracted and used as thickeners, gelling agents, etc., in food processing. Hu et al [ 7 ] and Tang et al [ 8 ] isolated the active components in TF and applied them as emulsifiers and thickeners to compound drinks, yogurt and other foods.…”
Section: Introductionmentioning
confidence: 99%
“…We can learn that among these substances, WJP has better emulsion stability and can maintain the emulsion effect for a longer period, even at different pH values, the emulsion stability of WJP is still the highest (J. Zhang et al, 2019). R. Tang et al (2020) combined WJP and Sophora flavescens extract and investigated the effect of WJP on the texture and rheological properties of low‐fat yogurt by adding different amounts of WJP. Through experimental exploration, it can be found that the addition of WJP in yogurt can work together with Sophora japonica extract to improve the rheological properties of low‐fat yogurt; not only that, the growth of Streptococcus thermophilus in yogurt is accelerated, and the fermentation time is also shortened.…”
Section: Applicationsmentioning
confidence: 99%